A Synthesis Between Phenomenological and Naturalism Approach in Interpreting Home: A Home Bubble Theory - Dimitry Ratulangie Ichwan; Embun Kenyowati Ekosiwi (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2023)
A phenomenological interpretation of home is usually done romantically, in which the home is thought to be a source of safety, comfort, and security. This conclusion about home is problematic, considering that if all of these components do not exist in a certain place, the home will dissipate. This research, which was conducted by using the synthesis of horizon method, aims to see if the concept of home can be understood through a new approach that weighs in natural law in human perception towards a certain spacetime. Through this method, home is formed along with the positive connection between a subject with a certain place in a certain spacetime. The memories and experiences of a subject towards a place allow their home bubble that is always carried by them to merge with the bubbles in the environment. The more frequently this merger happens, the subject will have access to more varieties of time. Hence, through this phenomeno-naturalistic perspective, home is defined as a bubble that is dynamic, transformative, and has the ability to be physical and metaphysical entities.